سورہ التوبۃ میں تاریخی پہلوؤں سے متعلق آیات کی تاویل میں ابن کثیر کا منہجIbn Kathīr's Approach towards Interpretation of Verses related to Historical Aspects in Surah al-Tawbah (Al-Qamar, 2022)
This article studies Ibn Kathīr's Approach towards Interpretation of Verses related to Historical Aspects in Sūrah al-Tawbah. It argues that in his commentary, Ibn Kathīr has adopted three types of methodologies in the interpretation of the relevant verses: First one is narrative methodology, in which the interpretation of the words mentioned in the verse, the background of the event, the hadīths related to the relevant discussion, the sayings of the Companions and scholars are mentioned, the second one is the comparative methodology, in which the differences in the interpretation of the words, different opinions in the narration of events, the position of the jurists related to the rulings, and the comparison of the differences of the scholars in various other studies are mentioned, and the third one is the analytical methodology, under which the different opinions are described, in which  Ibn Kathīr sometimes presents his own analysis of the different existing theories on the relevant subject.
Keywords: Ibn Kathīr; Approach; Interpretation of Verses; Sūrah al-Tawbah